A case-control study of the risk factors for fistula-in-ano in infants and toddlers - Yanting Sun; Hongtao Liang; Shuang Hao; Lu Yin; Yibin Pan; Chen Wang; Jingen Lu (BMC, 2024)
Abstract Background Limited data are available regarding the risk factors for fistula-in-ano (FIA) in infants and toddlers, potentially affecting their daily lives. Objectives The purpose of this study was to identify potential risk factors for FIA in infants and toddlers, in order to implement early preventive interventions, avoid disease progression, and develop therapeutic strategies. Design and settings A retrospective case-control study was conducted, comparing 41 infants and toddlers diagnosed with FIA with 41 healthy controls, between August 2020 and December 2021. Independent variables (a) maternal characteristics during pregnancy and delivery, (b) perinatal characteristics, dietary behaviors, and defecation-related behaviors in infants and toddlers, (c) family dietary behaviors. Results Mothers of infants and toddlers with FIA had given birth more times in the past, while the infants and toddlers themselves had less mealtime, a higher rate of exclusive breastfeeding, frequent loose stools, and a larger proportion of used wipes, experiencing perianal skin anomalies. The logistic regression analysis revealed that there are four significant risk factors associated with the development of FIA in infants and toddlers, including the number of previous deliveries by the mother (OR 6.327), defecation frequency score (OR 5.351), stool consistency score (OR 5.017), and cleaning with wipes after defecation (OR 8.089). Conclusion Based on our data, it appeared that FIA in infants and toddlers could be attributed to several factors. These included an increased number of previous deliveries by mothers, frequent loose stools, and repeated wipe use. To prevent the occurrence and worsening of the disease, it is important to improve the frequency and consistency of stooling and provide proper care. Further research is required to verify these findings in other clinical settings.